Hydrophobic wear-resistant high-transmittance film and preparation method thereof
By using PC and PET materials in optical films and combining nano-oligosilsesquioxane (POSS), a multi-layer coextrusion structure is designed, and the film wear resistance, hydrophobicity and light transmittance in the prior art are solved. The problem of insufficient results enables high-performance hydrophobic, wear-resistant, and high-light transmission films.
Patent Information
- Application Number
- CN202411759478.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art is difficult to improve the hydrophobicity, self-cleaning performance and wear resistance while maintaining high light transmittance of the optical film. The processing technology is complex and the long-term performance stability is insufficient.
Using polycarbonate (PC) and polyethylene terephthalate (PET) as the basic raw materials, the multi-layer coextrusion structure is designed to form a support through the combination of nano-oligosilsesquioxane (POSS). The layer and functional layer enhance the wear resistance, hydrophobicity and light transmittance of the film.
It realizes excellent mechanical properties, optical properties and surface functionality of the film, has high light transmittance (more than 85%), high wear resistance, hydrophobicity and self-cleaning properties, and is suitable for high-demand industrial fields.
Smart Images

Figure CN119408269A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester films, and in particular to a hydrophobic, wear-resistant and highly light-transmittance film and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, people have put forward higher and higher requirements for the functionality of thin films, especially in the fields of consumer electronics, optical equipment, building materials and automotive industries that have high requirements for material performance. Hydrophobic materials can effectively reduce the interaction between the surface and water molecules, so that water droplets form a high contact angle on the surface and roll off quickly, thereby avoiding the accumulation of water stains and dirt. This performance is particularly important in applications such as electronic display screens, touch panels and building windows that need to remain clean for a long time. Traditional hydrophobic coating materials are mostly achieved by coating with fluorinated polymers or siloxane compounds, which can effectively reduce surface energy and achieve a self-cleaning effect. However, although fluorinated coatings have excellent hydrophobic properties, their environmental friendliness has been widely questioned, especially the harmful perfluorinated compounds (PFOA, etc.) that may be produced during their preparation. Therefore, in recent years, the development of fluorine-free alternative materials with the same or better hydrophobic properties has become a research hotspot. Polysilsesquioxane (POSS) is an inorganic-organic hybrid material with low surface energy. It has excellent hydrophobicity and shows advantages in environmental protection and biocompatibility. It is one of the ideal candidates for the next generation of hydrophobic materials.
[0003] Optical films are important components of electronic devices. They are often susceptible to friction, scratches and wear in daily use, resulting in performance degradation. For optical devices, insufficient wear resistance will directly affect their light transmittance, image clarity and overall aesthetics. Therefore, improving the wear resistance of optical films is a key issue in the manufacture of optical components and electronic devices. POSS molecules have a cage-like organic-inorganic hybrid structure. The inorganic part of this structure (silicon oxygen skeleton) gives the material high strength and wear resistance, while the organic part can give the material different functionalities through chemical modification. Compared with traditional inorganic wear-resistant materials, its organic-inorganic-hybrid structure can have better compatibility and adjustability with the base film. At the same time, compared with traditional inorganic wear-resistant materials such as silica, its molecular size is small and has little effect on the light transmittance of the film. In addition, the nanostructure of POSS wear-resistant materials exhibits the characteristics of high wear resistance, light weight, excellent light transmittance, flexible functionalization and easy processing, and has many significant advantages over other wear-resistant materials in film applications.
[0004] Polycarbonate (PC) and polyethylene terephthalate (PET) are two common optical film materials, widely used in electronic displays, touch screens, optical lenses, etc. Although PET is widely used due to its low cost and stable physical properties, PC has much higher toughness than PET and is suitable for use as an optical film that is subjected to external forces for a long time, and its light transmittance is higher than PET.
[0005] In the prior art, there is a technology of preparing a composite film of PC and PET for use on the surface of optical devices. For example, the invention CN109367176A discloses a scratch-resistant transparent film, a scratch-resistant surface product and a composite sheet, comprising a PMMA layer located on the upper layer and a PET layer arranged on the lower surface of the PMMA layer, and the lower surface of the PET layer is provided with a PMMA layer or a PC layer or a PC layer and a PMMA layer. However, the invention does not take into account the demand for hydrophobic properties of optical device materials in the design, so it has obvious deficiencies in application scenarios that require self-cleaning, waterproofing and anti-fouling.
[0006] Invention CN106883439B discloses a modified high anti-reflection optical film and a preparation method thereof, wherein the invention introduces a cage-type polysilsesquioxane structure (POSS) containing amino groups into a fluorine-containing emulsion polymer, synthesizes a fluorine-containing emulsion copolymer with an optical anti-reflection function, and the latex particles in the emulsion are evenly distributed on the surface of the substrate, and the latex is applied to the surface of the polyester substrate, and a large number of nanoscale pores are formed on the surface of the substrate through the action of the cage-type polysilsesquioxane structure, so that the effective refractive index is low, thereby playing an optical anti-reflection function. However, the invention utilizes the cage-type polysilsesquioxane structure (POSS) material in the form of a coating, and the anti-reflection effect depends on the uniform distribution of the fluorine-containing emulsion polymer, and the coating process has high requirements, and the mechanical properties and wear resistance of the material are limited, and the coating layer is easy to gradually lose as the use time increases, resulting in performance degradation.
[0007] Therefore, how to improve the hydrophobicity, self-cleaning performance and wear resistance of PET and PC composite optical films while maintaining high light transmittance based on their structure and performance characteristics, and achieve long-term performance stability of the materials through a simpler processing technology has become a key issue that technical personnel in this field need to solve urgently. Summary of the invention
[0008] In view of the defects existing in the above-mentioned prior art, the present invention provides a hydrophobic, wear-resistant and highly light-transmittance film and a preparation method thereof. The hydrophobic, wear-resistant and highly light-transmittance film is based on PC and PET as raw materials. Through the use of nano-oligomeric silsesquioxane, the film has excellent wear resistance, hydrophobicity, self-cleaning and high transparency. It is particularly suitable for fields with high requirements on comprehensive material performance, such as consumer electronics, optical equipment, building materials and automotive industries.
[0009] In a first aspect, the present invention provides a hydrophobic, wear-resistant and highly light-transmittant film, comprising a stacked support layer and a functional layer;
[0010] A support layer comprising at least one of polycarbonate, polyethersulfone, thermoplastic polyurethane, and cycloolefin polymer;
[0011] a functional layer comprising polyethylene terephthalate and nano-oligomeric silsesquioxane;
[0012] The content of the nano oligomeric silsesquioxane is 1%-5% of the total mass of the functional layer, including at least one of trisilanol isooctyl-POSS, trisilanol phenyl-POSS, octaphenyl-POSS and dodecanyl-POSS;
[0013] The hydrophobic, wear-resistant and highly light-transmitting film is prepared by multi-layer co-extrusion, has a light transmittance of more than 80%, and a water contact angle of more than 100°.
[0014] The supporting layer of the present invention adopts polycarbonate (PC), polyethersulfone (PES), thermoplastic polyurethane (TPU) and cycloolefin polymer (COC), which are all supporting materials with excellent mechanical properties and light transmittance. The functional layer adopts polyethylene terephthalate (PET) as a substrate and adds 1%-5% of nano oligomeric silsesquioxane (POSS) to form a hydrophobic and wear-resistant protective layer on the surface of the film, which not only makes water droplets form a high contact angle on the surface and roll off quickly to achieve a self-cleaning effect, but also significantly enhances the scratch resistance. At the same time, the specific type and content of POSS are controlled to avoid affecting the optical transmittance of the film, thereby achieving the coordinated optimization of mechanical properties, optical properties and surface functionality.
[0015] Preferably, the support layer comprises polycarbonate and has a thickness of 10-50 μm;
[0016] The thickness of the functional layer is 10-40 μm;
[0017] The light transmittance of the hydrophobic, wear-resistant and highly light-transmittance film is above 85%, preferably above 88%; the water contact angle is above 105°, preferably between 110° and 125°.
[0018] Preferably, under 1000 cycles of CS-10 grinding wheel and 500g load, the mass loss of the hydrophobic, wear-resistant and highly light-transmittance film is less than 15mg, preferably less than 12mg.
[0019] Preferably, the functional layer further comprises a compatibilizer, the content of which is 2%-9% of the total mass of the functional layer;
[0020] The compatibilizer includes at least one of maleic anhydride grafted polypropylene, SEBS grafted maleic anhydride, ethylene-vinyl acetate grafted maleic anhydride and epoxidized polypropylene.
[0021] The compatibility of PET and PC at the double-layer interface is improved by using a compatibilizer, thereby increasing the interlayer bonding strength and ensuring the long-term stability of the film.
[0022] Preferably, the nano oligomeric silsesquioxane is compounded by at least two of a first POSS, a second POSS, and a third POSS, wherein:
[0023] The first POSS includes trisilanolphenyl-POSS;
[0024] The second POSS includes at least one of octaphenyl-POSS and dodecanphenyl-POSS;
[0025] The third POSS includes trisilanol isooctyl-POSS.
[0026] Nano oligomeric silsesquioxane can exhibit the characteristics of high wear resistance, light weight, excellent light transmittance, flexible functionality and easy processing, and its cage-like organic-inorganic hybrid structure enables it to have better and more flexible comprehensive performance, wherein the inorganic part (silicon oxygen skeleton) gives the material high strength and wear resistance, while the organic part can give the material different functionalities through chemical modification. Compared with traditional inorganic wear-resistant materials, its organic-inorganic-hybrid structure can have better compatibility and adjustability with the base film, and compared with traditional inorganic wear-resistant materials such as silicon dioxide, its molecular size is small and has little effect on the light transmittance of the film. Based on the respective characteristics of the above-mentioned oligomeric silsesquioxanes, the present invention further compounded them for use, so as to better demonstrate the positive effect of oligomeric silsesquioxanes in composite films.
[0027] Preferably, the oligomeric silsesquioxane is compounded with the first POSS, the second POSS and the third POSS in a mass ratio of (3-6):(2-4):(2-4).
[0028] The larger steric hindrance effect of the phenyl groups in the trisilanolphenyl-POSS of the first POSS, the octaphenyl-POSS of the second POSS, and the dodecaphenyl-POSS can enhance the interaction between molecules, thereby significantly improving the wear resistance of the film. Secondly, the phenyl structure has good optical transparency, and the POSS molecule itself is small in size, so the introduction of POSS into the film will not significantly affect the transmittance, so that the composite film can obtain better wear resistance while maintaining high transparency. In the third POSS, the isooctyl group of trisilanol isooctyl-POSS provides significant hydrophobicity, forming a nano protective layer with low surface energy on the surface of PET, which significantly improves the hydrophobicity and self-cleaning effect of the film. When the total amount of oligomeric silsesquioxane is controlled at 1%-5% of the total mass of the functional layer, a relatively ideal balance can be achieved between hydrophobicity, wear resistance, compatibility and dispersibility.
[0029] Specifically, the trisilanol phenyl-POSS in the first POSS, the silanol group (-Si-OH) can form an intermolecular force with the C=O on the PET molecular chain or the -OH of the terminal group through hydrogen bonding, which helps to improve the compatibility of the two and the uniformity of the dispersion of POSS in the PET matrix, and can also significantly improve the rigidity and strength of PET while maintaining a certain toughness. In addition, the synergistic effect of the phenyl group and the silanol group helps to improve the thermal stability and heat deformation temperature of PET, and has a wider operating temperature range.
[0030] For the second POSS, the polarity of the C=O group of PET is relatively strong, while the polarity of octaphenyl-POSS and dodecanyl-POSS is extremely low, resulting in slightly lower compatibility with PET. However, octaphenyl-POSS and dodecanyl-POSS have outstanding effects on enhancing the thermal stability, mechanical strength and flame retardant properties of the polymer matrix. Therefore, when selecting, the present invention preferably pre-epoxidizes the octaphenyl-POSS and dodecanyl-POSS.
[0031] Preferably, the second POSS is subjected to epoxidation treatment, comprising the following steps:
[0032] S1, add the second POSS, epichlorohydrin, and alkaline catalyst in order to anhydrous tetrahydrofuran and stir, and heat to reflux to obtain a mixed solution;
[0033] S2, cooling the mixed solution and washing it with an inorganic solvent until the washing solution is neutral, and then drying and removing the inorganic solvent to obtain a crude product;
[0034] S3, the crude product is evaporated and dried under reduced pressure to remove the organic solvent, so as to obtain the second POSS treated by epoxidation.
[0035] More preferably, in step S1, the second POSS, epichlorohydrin and alkaline catalyst are added in steps, wherein the second POSS is added to anhydrous tetrahydrofuran solvent under a nitrogen atmosphere and fully stirred, and then epichlorohydrin is slowly added dropwise within 5-12 minutes and fully stirred; finally, the alkaline catalyst is added and the solvent is placed in a nitrogen atmosphere, and is subjected to a constant temperature heating reflux treatment in an oil bath at 50-70° C. for 6-8 hours;
[0036] The inorganic solvent in step S2 includes an inorganic acid solution and deionized water, wherein the inorganic acid solution is preferably a hydrochloric acid solution; anhydrous sodium sulfate is preferably used to dry the organic phase, and the desiccant is filtered to remove the desiccant.
[0037] For the 3rd POSS, isooctyl is a nonpolar alkyl chain, has stronger hydrophobicity, but it is less compatible with the polar molecular chain of PET, and the excessive amount of trisilanol isooctyl-POSS in PET easily weakens the dispersibility, thus the present invention adds the 3rd POSS in the synthetic PET process, makes it be dispersed in small molecule polymerization monomer in advance, in ethylene glycol and terephthalic acid polymerization process, trisilanol isooctyl-POSS is embedded between PET molecular chains, forms in-situ dispersion and is evenly deposited in the PET matrix, on the one hand avoids the agglomeration phenomenon of adding the 3rd POSS afterwards. On the other hand, the POSS structure molecular scale introduced by in-situ dispersion is smaller, and the optical transparency of PET can not be significantly affected after being evenly dispersed, and the dispersion of the 3rd POSS is conducive to reducing the crystallization trend of PET, is conducive to improving the light transmittance of PET.
[0038] Preferably, the third POSS is added during the preparation of polyethylene terephthalate to obtain modified polyethylene terephthalate, comprising the steps of:
[0039] The trisilanol isooctyl-POSS is mixed with ethylene glycol and a catalyst, and then mixed with terephthalic acid, heated, and vacuumed to react.
[0040] In a second aspect, the present invention further provides a method for preparing the hydrophobic, wear-resistant and highly light-transmittance film, comprising the following steps:
[0041] S1, drying each layer of raw materials;
[0042] S2, adding nano oligomeric silsesquioxane and an optional compatibilizer into PET, and mixing to obtain a functional layer co-extrusion material;
[0043] S3, adding the functional layer co-extruded material and the supporting layer raw material into the extruder respectively, melting and co-extruding to obtain a thick sheet;
[0044] S4, stretching the thick sheet to obtain the hydrophobic, wear-resistant and highly light-transmittance film.
[0045] Preferably, in step S2, the extrusion screw speed is 60-90 r / min, preferably 70-80 r / min, and the temperature is 260-300° C., preferably 270-290° C.; and / or
[0046] In the coextrusion of step S3, the support layer raw material is added to the main extruder at a temperature of 260-290°C; the functional layer coextrusion material is added to the auxiliary extruder at a temperature of 255-285°C, preferably 270-285°C.
[0047] Preferably, in the co-extrusion of step S3, the extruder die is loaded with an electrostatic voltage of 6-7 kV, the cold roller temperature is below 20°C, the cold roller speed is 10-20 m / min, and the thickness of the obtained thick sheet is 500-1200 μm. The die is loaded with static electricity so that the extrudate is accurately attached to the cold roller and the temperature is rapidly reduced to increase the supercooling degree, thereby effectively reducing the crystallinity of the thick sheet.
[0048] Preferably, in step S4, stretching the thick sheet includes:
[0049] S4.1 Preheat the thick sheet at 80-120℃ for 30-90s;
[0050] S4.2 performing synchronous biaxial stretching on the preheated thick sheet at a stretching temperature of 110-140° C., with an X-axis to Y-axis stretching ratio of (3-4):1, to obtain a stretched film;
[0051] S4.3 The stretched film is shaped at a temperature of 100-120°C.
[0052] The present invention has at least the following beneficial effects:
[0053] (1) The present invention achieves excellent mechanical properties, optical properties and surface functionality of the film through the multilayer structure design of the support layer and the functional layer, combined with the synergistic effect of high-performance materials PC, PET and nano oligomeric silsesquioxane (POSS). While ensuring high light transmittance (above 85%), the film has excellent wear resistance, hydrophobicity and structural stability, and is suitable for optics, electronics and high-demand industrial protection fields.
[0054] (2) The present invention significantly enhances the interfacial bonding force between the polar and non-polar materials between the film layers and within the layers by compounding trisilanol phenyl-POSS, octaphenyl-POSS and / or dodecanyl-POSS and trisilanol isooctyl-POSS, and in particular selects a specific compounding and introduction method according to the characteristics of each POSS, thereby improving the dispersibility and uniformity, and ensuring uniform and stable hydrophobic, wear-resistant, high light transmittance and comprehensive mechanical properties of the film product, including:
[0055] The second POSS was epoxidized to introduce active epoxy groups on its surface, which significantly enhanced the interface compatibility and chemical stability between the second POSS and the matrix material, and further improved the wear resistance and thermal stability of the film.
[0056] The third POSS is introduced into PET by in-situ dispersion, which ensures the uniform dispersion of POSS in the matrix and avoids the performance degradation caused by particle aggregation. It not only improves the mechanical properties and surface hydrophobicity of the film, but also maintains high transmittance and excellent optical properties, combining process simplification and long-term performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a schematic structural diagram of the hydrophobic, wear-resistant and highly light-transmittance film of the present invention.
[0058] Figure 2 This is a physical picture of the hydrophobic, wear-resistant and highly light-transmittance film of the present invention.
[0059] Reference numerals: 1 - support layer, 2 - functional layer. DETAILED DESCRIPTION
[0060] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with the specification and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0061] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0062] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0063] The following will be combined with the attached Figure 1-2 The hydrophobic, wear-resistant and highly light-transmittance film provided by the present invention and the preparation method thereof are described.
[0064] A hydrophobic, wear-resistant, and highly transparent film, see attached Figure 1 ,include:
[0065] (1) The support layer 1 has a thickness of 10-50 μm and comprises at least one of polycarbonate, polyethersulfone, thermoplastic polyurethane and cycloolefin polymer.
[0066] (2) a functional layer 2 having a thickness of 10-40 μm, comprising polyethylene terephthalate and 1%-5% of nano-oligomeric silsesquioxane by weight, and an optional compatibilizer;
[0067] The compatibilizer, whose content is 2%-9% of the total mass of the functional layer 2, includes at least one of maleic anhydride grafted polypropylene, SEBS grafted maleic anhydride, ethylene-vinyl acetate grafted maleic anhydride and epoxidized polypropylene.
[0068] The nano oligomeric silsesquioxane comprises at least one of trisilanol isooctyl-POSS, trisilanol phenyl-POSS, octaphenyl-POSS and dodecanyl-POSS.
[0069] Based on the property differences of different types of nano oligomeric silsesquioxanes, the nano oligomeric silsesquioxanes of the present invention are preferably compounded, that is, compounded by at least two of the first POSS, the second POSS, and the third POSS, more preferably compounded by the first POSS, the second POSS, and the third POSS in a mass ratio of (3-6): (2-4): (2-4), wherein:
[0070] (1) The first POSS includes trisilanol phenyl-POSS, which has good compatibility with the PET matrix and can be directly added to PET for blending;
[0071] (2) a second POSS, comprising at least one of octaphenyl-POSS and dodecanphenyl-POSS, wherein the second POSS is pre-epoxidized to significantly improve compatibility with the PET matrix, and is added to the PET for blending after the pre-treatment;
[0072] (3) The third POSS includes trisilanol isooctyl-POSS. Trisilanol isooctyl-POSS has excellent hydrophobicity, but its compatibility with the PET matrix needs to be further improved. Therefore, it is added to PET through an in-situ dispersion method, which specifically includes: mixing trisilanol isooctyl-POSS with ethylene glycol and a catalyst, and then mixing with terephthalic acid, heating, and vacuuming to react to prepare modified polyethylene terephthalate.
[0073] Wherein, the octaphenyl-POSS and / or dodecanphenyl-POSS of the second POSS is subjected to epoxidation treatment, specifically comprising the following steps:
[0074] S1, add 0.5-0.8mmol of the second POSS and an appropriate amount of anhydrous tetrahydrofuran solvent (about 15-25ml) into a three-necked flask, and stir under nitrogen protection to completely dissolve;
[0075] S2, epichlorohydrin is slowly added dropwise in a flask, the molar ratio of epichlorohydrin to the second POSS is about (3-6): 1, the dropping time is controlled at 5-10min, and stirring is continued for 20-35min after the dropping is completed;
[0076] S3, adding a base catalyst (KOH and / or NaOH), the molar ratio of the base catalyst to the second POSS is (1-3): 1;
[0077] S4. Heat the reaction mixture to reflux in an oil bath at 60±2° C. for 6-8 hours, maintain constant temperature, and continue stirring under nitrogen protection;
[0078] S5. After the reaction is completed, the reaction solution is cooled to room temperature;
[0079] S6, washing the organic phase with an inorganic acid solution, preferably a hydrochloric acid solution, to neutralize the residual alkaline catalyst; then washing with deionized water for 3-5 times until the washing liquid is neutral; drying the organic phase with anhydrous sodium sulfate, and then filtering to remove the desiccant;
[0080] S7, removing anhydrous tetrahydrofuran solvent by rotary evaporation of the filtrate under reduced pressure;
[0081] S8. Dry the residue in a vacuum drying oven to obtain a second POSS functionalized with epoxy groups.
[0082] The following preparation method is provided for the hydrophobic, wear-resistant and highly light-transmittance film, which specifically comprises the following steps:
[0083] S1, drying the optical grade PET slices at 100-150° C. for 6-24 hours, and drying the nano oligomeric silsesquioxane powder in a freeze dryer for 6-24 hours to remove moisture;
[0084] S2, adding nano oligomeric silsesquioxane and an optional compatibilizer to PET, and preparing a functional layer co-extrusion material by melt blending using a micro twin-screw extruder, wherein the screw speed is set to 60-90 r / min and the temperature is set to 260-300° C.;
[0085] S3, adding the functional layer co-extruded material to the auxiliary twin-screw extruder silo, the extrusion temperature of the auxiliary extruder is 255-285°C, preferably 265-275°C; adding the PC slices to the main twin-screw extruder silo, the extrusion temperature of the main extruder is 260-290°C, preferably 270-285°C, and melt co-extruded to obtain a thick sheet;
[0086] The extruder die is loaded with an electrostatic voltage of 6-7 kV, the cold roller temperature is below 20°C, the cold roller speed is 10-20 m / min, and the obtained thick sheet has a thickness of 500-1200 μm and a crystallinity within 3%;
[0087] S4, stretching the thick sheet, including:
[0088] S4.1 Preheat the thick sheet at 80-120℃ for 30-90s;
[0089] S4.2 The preheated thick sheet is subjected to synchronous biaxial stretching at a stretching temperature of 110-140° C., with an X-axis to Y-axis stretching ratio of (3-4):1, to obtain a stretched film; the X-axis and the Y-axis are mutually perpendicular axes, which may also be referred to as the transverse axis (TD) and the longitudinal axis (MD);
[0090] S4.3 The stretched film is shaped at a temperature of 100-120°C.
[0091] Example 1
[0092] A hydrophobic, wear-resistant and highly light-transmittance film, comprising:
[0093] (1) Support layer, thickness is 10 μm, PC is selected;
[0094] (2) a functional layer having a thickness of 10 μm, and comprising PET, trisilanol isooctyl-POSS accounting for 3% of the total weight of the functional layer, and maleic anhydride grafted polypropylene compatibilizer accounting for 5% of the total weight of the functional layer;
[0095] The method for preparing the hydrophobic, wear-resistant and highly light-transmittance film specifically comprises the following steps:
[0096] S1, drying the optical grade PET slices at 120°C for 12 hours, and drying the trisilanol phenyl-POSS powder in a freeze dryer for 12 hours to remove moisture;
[0097] S2, adding trisilanol phenyl-POSS and compatibilizer into PET, and preparing functional layer co-extrusion material by melt blending using a micro twin-screw extruder, wherein the screw speed is set to 75r / min and the temperature is set to 280°C;
[0098] S3, adding the functional layer co-extruded material into the auxiliary twin-screw extruder silo, the extrusion temperature of the auxiliary extruder is 270°C; adding the PC slices into the main twin-screw extruder silo, the extrusion temperature of the main extruder is 280°C;
[0099] Melt coextrusion to obtain thick sheets;
[0100] The extruder die was loaded with an electrostatic voltage of 6.5 kV, the cold roller temperature was 15 ± 1 ° C, and the cold roller speed was 15 m / min to obtain a co-extruded thick sheet;
[0101] S4, performing synchronous biaxial stretching on the thick sheet comprises:
[0102] S4.1 Preheat the thick sheet at 100°C for 60 seconds;
[0103] S4.2 performing synchronous biaxial stretching on the preheated thick sheet at a stretching temperature of 125°C with an X-axis to Y-axis stretching ratio of 3.5:1 to obtain a stretched film;
[0104] S4.3 The stretched film is shaped at a temperature of 110°C.
[0105] Example 2-3
[0106] The difference between Example 2-3 and Example 1 is that the thickness of the coextruded thick sheet is different, and after the simultaneous biaxial stretching, the thickness of the obtained support layer and functional layer are different.
[0107] Embodiment 4-5
[0108] The difference between Example 4-5 and Example 1 is that the content of nano oligomeric silsesquioxane in the functional layer is different.
[0109] Example 6
[0110] The difference between Example 6 and Example 1 is that the nano oligomeric silsesquioxane uses only octaphenyl-POSS that has been epoxidized, and the epoxidation treatment includes the following steps:
[0111] S1. Add 0.6 mmol of octaphenyl-POSS and 20 ml of anhydrous tetrahydrofuran solvent into a three-necked flask, and stir under nitrogen protection to completely dissolve the mixture;
[0112] S2. Slowly drop epichlorohydrin into the flask, the molar ratio of epichlorohydrin to octaphenyl-POSS is about 5:1, the dropping time is controlled within 10 minutes, and stirring is continued for 30 minutes after the dropping is completed;
[0113] S3, adding KOH catalyst, the molar ratio of KOH to octaphenyl-POSS is 2:1;
[0114] S4. Heat the reaction mixture to reflux in an oil bath at 60±2° C. for 6 hours, maintain constant temperature, and continue stirring under nitrogen protection;
[0115] S5. After the reaction is completed, the reaction solution is cooled to room temperature;
[0116] S6. Wash the organic phase with hydrochloric acid solution to neutralize the residual KOH; then wash with deionized water for 3-5 times until the washing solution is neutral; dry the organic phase with anhydrous sodium sulfate, and then filter to remove the desiccant;
[0117] S7, removing anhydrous tetrahydrofuran solvent by rotary evaporation of the filtrate under reduced pressure;
[0118] S8. Dry the residue in a vacuum oven to obtain epoxy-functionalized octaphenyl-POSS.
[0119] Example 7
[0120] The difference between Example 7 and Example 1 is that the nano oligomeric silsesquioxane only uses trisilanol isooctyl-POSS, and the trisilanol isooctyl-POSS is in-situ dispersed in the PET matrix, including:
[0121] The trisilanol isooctyl-POSS is mixed with ethylene glycol and a catalyst, and then mixed with terephthalic acid, heated, and vacuumed to react to prepare modified polyethylene terephthalate.
[0122] Examples 8-12
[0123] The difference between Examples 8-12 and Example 1 is that the nano-oligomeric silsesquioxane is compounded, wherein the first POSS is trisilanol phenyl-POSS; the second POSS is epoxidized octaphenyl-POSS; the third POSS is trisilanol isooctyl-POSS, and they are dispersed in situ in the PET matrix.
[0124] Examples 13-14
[0125] The difference between Examples 13-14 and Example 10 is that the stretching ratio is different.
[0126] Comparative Example 1-2
[0127] The difference between Comparative Example 1-2 and Example 1 is that the content of nano-oligomeric silsesquioxane in the functional layer is different.
[0128] The main parameters of Examples 1-14 and Comparative Examples 1-2 are shown in Table 1:
[0129] Table 1
[0130]
[0131] Performance Testing:
[0132] (1) Light transmittance: tested in accordance with ISO13468 standard using German BYK HAZE-gard i.
[0133] (2) Hydrophobicity (water contact angle): The test was conducted using the G-1 εrma angle meter contact angle tester produced by Kyowa Co., Ltd. Deionized water was used and a water drop was dropped on the film surface for 1 minute before the test. For each sample, three points with a spacing of 5 mm were measured, and a total of 6 readings were taken, and the arithmetic average was taken.
[0134] (3) Abrasion resistance: The mass loss of the composite films was measured using a CS-10 grinding wheel and a 500 g load for 1000 cycles.
[0135] (4) Mechanical properties: Tensile strength and elongation at break were tested according to ASTM D882.
[0136] The above test was performed on Examples 1-14 and Comparative Examples 1-2. The test results are shown in Table 2:
[0137] Table 2
[0138] Light transmittance / % Water contact angle Mass loss / mg Tensile strength / Mpa Example 1 90.3 115° 9.6 170 Example 2 89.8 114° 9.4 195 Example 3 90.1 117° 9.4 181 Example 4 87.7 118° 9.2 179 Example 5 90.5 112° 10.8 185 Example 6 89.1 118° 6.5 186 Example 7 88.5 120° 8.5 189 Example 8 90.1 116° 7.3 190 Example 9 89.3 119° 8.8 181 Example 10 90.3 118° 8.0 185 Embodiment 11 90.5 117° 8.4 187 Example 12 88.1 119° 7.8 182 Example 13 90.0 118° 8.0 184 Embodiment 14 89.8 118° 8.2 182 Comparative Example 1 90.6 100° 12.2 171 Comparative Example 2 83.2 120° 9.0 173
[0139] According to the test results of Table 2, the comprehensive performance of embodiments 1-14 is excellent, and the transmittance is more than 80%, preferably more than 85%. Most embodiments, especially the samples using compound POSS, can reach more than 88%. In terms of hydrophobicity, the water contact angle is greater than 100°, preferably greater than 110°, and the film has excellent hydrophobic self-cleaning properties. In terms of wear resistance, the mass loss is less than 12mg, and most embodiments are less than 10mg, especially the samples containing the second POSS, and the overall wear resistance is better, and the mass loss is less than 9mg.
[0140] In Comparative Example 1, the content of nano-oligomeric silsesquioxane is low. Although the optical properties are good, the hydrophobicity, wear resistance and mechanical properties are slightly insufficient. In Comparative Example 2, the content of nano-oligomeric silsesquioxane is too high, which easily leads to a decrease in dispersion uniformity, and the transmittance and mechanical properties are negatively affected.
[0141] In summary, the present invention significantly enhances the interfacial bonding force between polar and non-polar materials between and within film layers by appropriately adding nano-oligomeric silsesquioxane and compatibilizer, and in particular, by selecting a specific compounding ratio and introduction method according to the characteristics of each POSS, thereby improving the dispersibility and uniformity, and ensuring that the film product has uniform and stable hydrophobic, wear-resistant, high light transmittance and comprehensive mechanical properties.
[0142] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention is intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention.
Claims
1. A hydrophobic, wear-resistant and highly light-transmittance film, characterized in that: comprising a stacked support layer and a functional layer; A support layer comprising at least one of polycarbonate, polyethersulfone, thermoplastic polyurethane, and cycloolefin polymer; a functional layer comprising polyethylene terephthalate and nano-oligomeric silsesquioxane; The content of the nano oligomeric silsesquioxane is 1%-5% of the total mass of the functional layer, including at least one of trisilanol isooctyl-POSS, trisilanol phenyl-POSS, octaphenyl-POSS and dodecanyl-POSS; The hydrophobic, wear-resistant and highly light-transmitting film is prepared by multi-layer co-extrusion, has a light transmittance of more than 80%, and a water contact angle of more than 100°.
2. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 1, characterized in that: The support layer includes polycarbonate and has a thickness of 10-50 μm; The thickness of the functional layer is 10-40 μm; The hydrophobic, wear-resistant and highly light-transmittance film has a light transmittance of more than 85%, a water contact angle of more than 105° and a tensile strength of more than 170 MPa.
3. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 1 or 2, characterized in that: The functional layer also includes a compatibilizer, the content of which is 2%-9% of the total mass of the functional layer; The compatibilizer includes at least one of maleic anhydride grafted polypropylene, SEBS grafted maleic anhydride, ethylene-vinyl acetate grafted maleic anhydride and epoxidized polypropylene.
4. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 1 or 2, characterized in that: The nano oligomeric silsesquioxane is compounded by at least two of a first POSS, a second POSS, and a third POSS, wherein: The first POSS includes trisilanolphenyl-POSS; The second POSS includes at least one of octaphenyl-POSS and dodecanphenyl-POSS; The third POSS includes trisilanol isooctyl-POSS.
5. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 4, characterized in that: The nano oligomeric silsesquioxane is compounded by the first POSS, the second POSS and the third POSS in a mass ratio of (3-6): (2-4): (2-4).
6. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 5, characterized in that: The second POSS is subjected to epoxidation treatment, comprising the following steps: S1, add the second POSS, epichlorohydrin, and alkaline catalyst in order to anhydrous tetrahydrofuran and stir, and heat to reflux to obtain a mixed solution; S2, cooling the mixed solution, washing with an inorganic solvent, and then drying to remove the inorganic solvent to obtain a crude product; S3, the crude product is evaporated and dried under reduced pressure to remove the organic solvent, so as to obtain the second POSS treated by epoxidation.
7. The hydrophobic, wear-resistant and highly light-transmittance film according to claim 5, characterized in that: The third POSS is added during the preparation of polyethylene terephthalate to obtain modified polyethylene terephthalate, comprising the following steps: The trisilanol isooctyl-POSS is mixed with ethylene glycol and a catalyst, and then mixed with terephthalic acid, heated, and vacuumed to react.
8. A method for preparing a hydrophobic, wear-resistant and highly light-transmittance film according to any one of claims 1 to 7, characterized in that: The steps include: S1, drying each layer of raw materials; S2, adding nano oligomeric silsesquioxane and an optional compatibilizer into PET, and mixing to obtain a functional layer co-extrusion material; S3, adding the functional layer co-extruded material and the supporting layer raw material into the extruder respectively, melting and co-extruding to obtain a thick sheet; S4, stretching the thick sheet to obtain the hydrophobic, wear-resistant and highly light-transmittance film.
9. The preparation method according to claim 8, characterized in that: In step S2, the extrusion screw speed is 60-90 r / min and the temperature is 260-300° C.; and / or In the co-extrusion of step S3, the support layer material is added to the main extruder at a temperature of 260-290° C.; the functional layer co-extrusion material is added to the auxiliary extruder at a temperature of 255-285° C.; and / or In the co-extrusion of step S3, the extruder die is loaded with an electrostatic voltage of 6-7 kV, the cold roller temperature is below 20° C., the cold roller speed is 10-20 m / min, and the thickness of the obtained thick sheet is 500-1200 μm.
10. The preparation method according to claim 8 or 9, characterized in that: In step S4, the thick sheet is stretched and processed including: S4.1 Preheat the thick slice at 80-120℃ and 30-90s; S4.2 Performing synchronous biaxial stretching on the preheated thick sheet at a stretching temperature of 110-140°C, with the X-axis to Y-axis stretching ratio being (3-4):1 to obtain a stretched film; S4.3 The stretched film is shaped at a temperature of 100-120°C.
Citation Information
Patent Citations
A modified high-reflection optical thin film and its preparation method
CN106883439B
Anti-scratch transparent film, anti-scratch surface product and composite sheet
CN109367176A
POSS (polyhedral oligomeric silsesquioxanes) modified high barrier three-layer co-extrusion packaging film and preparation method thereof
CN102019738A
Modified polycarbonate and preparation method thereof
CN102382439A
Anti-reflective film polarizing plate and display apparatus
CN111566523A
Cited By
Preparation and application of high-light-transmittance polycarbonate nanoparticle composite material
CN120310181A